Trans*: A quick and quirky account of gender variability - Halberstam, Jack (American studies now : critical histories of the present, 2018)
In the last decade, public discussions of transgender issues have increased exponentially. However, with this increased visibility has come not just power, but regulation, both in favor of and against trans people. What was once regarded as an unusual or even unfortunate disorder has become an accepted articulation of gendered embodiment as well as a new site for political activism and political recognition. What happened in the last few decades to prompt such an extensive rethinking of our understanding of gendered embodiment? How did a stigmatized identity become so central to U.S. and European articulations of self? And how have people responded to the new definitions and understanding of sex and the gendered body? In Trans*, Jack Halberstam explores these recent shifts in the meaning of the gendered body and representation, and explores the possibilities of a nongendered, gender-optional, or gender-queer future.
Keywords: approches et analyses; corps; cours; fem3200; identités LGBTQIA2+; personnes trans*; premier cycle; queer; ressource en ligne; thématiques; transféminisme

In a queer time and place: Transgender bodies, subcultural lives - Halberstam, Jack (J.) (New York University Press, 2005)
In a Queer Time and Place opens with a probing analysis of the life and death of Brandon Teena, a young transgender man who was brutally murdered in small-town Nebraska. After looking at mainstream representations of the transgender body as exhibited in the media frenzy surrounding this highly visible case and the Oscar-winning film based on Brandon's story, Boys Don’t Cry, Halberstam turns her attention to the cultural and artistic production of queers themselves. Halberstam examines the “transgender gaze,” as rendered in small art-house films like By Hook or By Crook, as well as figurations of ambiguous embodiment in the art of Del LaGrace Volcano, Jenny Saville, Eva Hesse, Shirin Neshat, and others. Halberstam then exposes the influence of lesbian drag king cultures upon hetero-male comic films, such as Austin Powers and The Full Monty, and, finally, points to dyke subcultures as one site for the development of queer counterpublics and queer temporalities. Considering the sudden visibility of the transgender body in the early twenty-first century against the backdrop of changing conceptions of space and time, In a Queer Time and Place is the first full-length study of transgender representations in art, fiction, film, video, and music. This pioneering book offers both a jumping off point for future analysis of transgenderism and an important new way to understand cultural constructions of time and place.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; cinéma; communication; cours; discipline; fem1000; har4600; identités LGBTQIA2+; lit4700; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme; états-unis; études culturelles